2020
DOI: 10.3390/ijms21051659
|View full text |Cite
|
Sign up to set email alerts
|

The ArathEULS3 Lectin Ends up in Stress Granules and Can Follow an Unconventional Route for Secretion

Abstract: Stress granules are cytoplasmic compartments, which serve as mRNA storage units during stress, therefore regulating translation. The Arabidopsis thaliana lectin ArathEULS3 has been widely described as a stress inducible gene. This study aimed to examine in detail the localization of ArathEULS3 lectin in normal and stressed cells. Colocalization experiments revealed that the nucleo-cytoplasmic lectin ArathEULS3 relocates to stress granules after stress. The ArathEULS3 sequence encodes a protein with a EUL lecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…The GUS and GFP localization assays in transgenic A. thaliana plants provided additional information about the possible function, in plants, of the AhN4L-1 protein. As previously reported for wheat germ agglutinin (WGA) (Mishkind et al, 1982;Dubiel et al, 2020a), the highly localized accumulation of both GUS and GFP signals in root tips was in concordance with the demonstrated defensive function of agglutinin-containing proteins against soil fungal pathogens (Mirelman et al, 1975). This localization also agreed with the anti-fungal effect against F. oxysporum, a notorious soil-borne pathogen of several plant crops, observed in overexpressing AhN4L-1 A. thaliana plants.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The GUS and GFP localization assays in transgenic A. thaliana plants provided additional information about the possible function, in plants, of the AhN4L-1 protein. As previously reported for wheat germ agglutinin (WGA) (Mishkind et al, 1982;Dubiel et al, 2020a), the highly localized accumulation of both GUS and GFP signals in root tips was in concordance with the demonstrated defensive function of agglutinin-containing proteins against soil fungal pathogens (Mirelman et al, 1975). This localization also agreed with the anti-fungal effect against F. oxysporum, a notorious soil-borne pathogen of several plant crops, observed in overexpressing AhN4L-1 A. thaliana plants.…”
Section: Discussionsupporting
confidence: 89%
“…This outcome was also incompatible with the robust induction of this gene in grain amaranth plants subjected to diverse abiotic stresses, with the reported transcript accumulation of several cucumber ATT protein genes in response to cold, drought, salt, and exogenous ABA treatment (Dang et al, 2017) and with the drought-responsive nature of a Natterin-4 gene in maize (Jin et al, 2019). It was also contrary to the response and stress-triggered re-localization into stress granules of an ABA-inducible A. thaliana Euonymus europaeus-related lectin, ArathEULS3, homologous to the E. europaeus agglutinin (Fouquaert et al, 2009), also activated by drought, salt, and osmotic stresses (Van Hove et al, 2015;Dubiel et al, 2020a) and to the tolerance to salt stress observed in A. thaliana transgenic plants overexpressing a soybean agglutinin presumed to interact with the core histones H2A, H2B, and H4 (Van Holle et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To approach this problem, we made use of the observation that stress granules (SGs) are formed at elevated temperatures in different plant tissues, e.g . roots, leaves and hypocotyls (Chodasiewicz et al, 2020; Dubiel et al, 2020; Hamada et al, 2018; Kosmacz et al, 2019; Modliszewski et al, 2018). It was previously shown that these SGs in Arabidopsis seedlings contain the cell cycle regulator CYCLIN-DEPENDENT KINASE A;1 (CDKA;1)(Kosmacz et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The HSP70 and SnRK1 kinase have been described as stress-dependent TSN2-interactors ( Gutierrez-Beltran et al, 2020 ). Lectin ArathEULS3 interactome analysis in A. thaliana revealed the presence of translational elongation factors, ribosomal, RNA-binding, and HSPs ( Dubiel et al, 2020 ).…”
Section: Sg-associated Proteinsmentioning
confidence: 99%